Lived experiences in the coping and recovery process of selected drug addicts in Peninsular Malaysia - Sadiron, Nazira (2015)
This study qualitatively examines the personal experiences of former drug addicts in order to close a gap in knowledge regarding the process of recovery, what are successful coping strategies, and what characteristics are associated with successful recovery from the point of view of persons in Mrecovery. A descriptive, phenomenological approach was taken to understanding the maintenance stage of recovery. Colaizzi’s Strategy was used as a framework for systematically analysing narrative texts obtained through in-depth and semi-structured interviews of six middle aged men from Peninsular Malaysia who had significant life experience with the trials and tribulations associated with remaining drug-free. The computer assisted, qualitative analysis software program ATLAS.ti was used to code, analyse, and make sense of their narratives. Through these texts,analysis of the respondents lived experiences in recovery process led to the identification of three emergent themes. These are (1) Process of Recovery Journey (2) Coping Strategies and (3) Characteristics of the Successful Recovery Person. There are three phases identified in recovery process which reflected as initial phase with experienced of dramatic relief which lead to turning point, self-awareness, self-reflection and inner conflict. Respondents identified these changes occurred in the working phases in the recovery process. These are include: Spiritual awakening,knowledge and skill, rebuilding dignity and elf- esteem and building and establishing social support. Respondents describe that this working phase as the most important part in changing an addicted person toward a non-addicted person in the recovery journey. The third phase is maintaining phase. Relationship with ‘recovery friends’ and by giving back to their families, especially their parents is also one of the importance factors to a maintaining their recovery. Respondent data identified specific coping styles in dealing with relapse risk factors, which are Problem-Focused Strategy,Appraisal-Focused Strategy, and Emotion-Focused Strategy. Characteristics of the successfully recovering substance abuser were found to fall into the following themes (1) the self after 5 years of recovery (2) expectation of success (3) expectation of relapse (4) new changes and (5) obstacles in recovery process. Knowing more about the life experiences found in the recovery process, what are coping strategies among successful substance abusers, and what are their characteristics and attributes has great potential to enhance understanding of substance abuse, reduce relapse rates,and improve the effectiveness of skills development in treatment centres throughout Malaysia.